A Review the Important of Green Human Resource Management Practices toward Employee Green Behaviour in Organization - Luh Titisari Dewi Adriana; Keke Tamara Fahira; Maulida Nailissa’adah; Hikmah El Maula (Journal of International Conference Proceedings (JICP), 2020)
Nowadays, the concerns of environment are becoming a very important global issue, including for organizations. The existence of an organization in the long term depends on the application of its environmental policies. Responding to a greater Environmental Awareness, organizations are becoming more concerned about managing green human resources (GHRM). Attention to employee green behavior appear from the employee’s necessities to use resources wisely and responsibly. Although the literature on GHRM gets a great attention and discussion among industry practitioner, however research that showed GHRM’s practice and its contribution to employee green behavior in organization is limited and requires more review in the academic literature. The aims of this research are (1) reviewed the literature on the relationship between GHRM practices and employee green behavior in organization; (2) explore the definitions provided by researchers regarding the term "GHRM" and present them to make interpretation of the GHRM concept. Secondary data and desk research methods are used in this study. The findings in this study highlight the status of green human resource practices such as green recruitment and selection, green training and development, green performance management, green involvement and green pay and reward simultaneously associated with the employee green human behavior both task or voluntary in the organization. Employee green behavior is considered to provide enormous benefits and does not damage the environment. This study provides a comprehensive literature review to measure human resource practices that can provide a broader focus for further research and for practitioners. Current study is more important for developing countries, which have alarming environmental issue and government regulations that have not been implemented properly.